Analysis on the data loading of utility data into the national utility database [compact disc] - 249399 Abd. Malik Abd. Latiff (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan (Geomatk) - Universiti Teknologi Malaysia, 2007